DIVERSITY OF FISH (PISCES) TYPES IN BARUAN RIVER VILLAGE JAYA BARU KECAMATAN SALANG KABUPATEN SIMEULUE - Orismi Loki; Meutia Zahara; Suwarniati Suwarniati; Aini Qurratu (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2021)
Baruan River is one of the rivers located in Jaya Baru Village, Salang District, Simeulue Regency, Aceh, Indonesia. The availability of related references regarding fish are still limited, especially freshwater fish in the Baruan River which is still not available. This study aims to determine the diversity of fish species in the Baruan River. The research was conducted from 9 June - 15 June 2019. The research method used was direct observation (inventory survey), by observing directly in the field where the research was located. Taking of fish samples is divided into three sample points. The tools used are fishing nets, fishing rods and traps. The results obtained 6 species from 120 individual fish; Gabus fish (Channa striata), Rice field eel (Monopterus albus), Mullet (Mugil cephalus), Betok / Papuyu (Anabas testudineus), Seriding (Ambassis nalua) and Laaya / Alabul (Acentrogobius caninus). Diversity index of fish species is H? = 1.532, this value is included in the medium category. While the evenness index value E? = 0.854, it means that the fish spread in the Baruan River is evenly distributed. The dominance index value is D = 0.756 or classified as low, meaning that there are no fish species that dominate the Baruan River. Keywords: Baruan River, diversity index, evenness, fish, dominance.